2005
DOI: 10.1128/jb.187.22.7667-7679.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Twin-Arginine Translocation Pathway of Mycobacterium smegmatis Is Functional and Required for the Export of Mycobacterial β-Lactamases

Abstract: Tuberculosis, caused by the bacillus Mycobacterium tuberculosis, remains a global health problem accounting for over two million deaths annually (23). The ability to survive in host phagocytes is a poorly understood virulence property of M. tuberculosis. The M. tuberculosis proteins exported to the bacterial cell surface or secreted by the bacillus are ideally positioned to interact with host cell components and include virulence factors that promote intracellular survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 83 publications
3
130
1
Order By: Relevance
“…In fact, tatC may be an essential gene for optimal growth in these bacteria (83,117). Recently, using β-lactamase as a reporter for Tat transport, McDonough et al (83) demonstrated that the phospholipase C proteins (PlcA and PlcB), important for the virulence of M. tuberculosis (83,104), are exported via the Tat pathway.…”
Section: Role In Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, tatC may be an essential gene for optimal growth in these bacteria (83,117). Recently, using β-lactamase as a reporter for Tat transport, McDonough et al (83) demonstrated that the phospholipase C proteins (PlcA and PlcB), important for the virulence of M. tuberculosis (83,104), are exported via the Tat pathway.…”
Section: Role In Pathogenesismentioning
confidence: 99%
“…Mycobacterium tuberculosis and Mycobacterium smegmatis tat mutants were unable to transport active β-lactamases (83). In fact, tatC may be an essential gene for optimal growth in these bacteria (83,117).…”
Section: Role In Pathogenesismentioning
confidence: 99%
“…In the high Guanine+Cytosine branch of Gram-positive bacteria known as actinomycetes, Tat is also apparently required for the translocation of lipoproteins, including the BlaC b-lactamase putative lipoprotein of Mycobacterium tuberculosis when it is expressed in M. smegmatis [16] and four putative lipoproteins in the model actinomycete, Streptomyces coelicolor [17]. Bioinformatic analysis indicates that Tat translocation of lipoproteins is widespread in the genus Streptomyces with up to 20% of putative lipoproteins being exported via Tat in the four currently sequenced Streptomyces species (M.I.H and I.C.S, unpublished).…”
Section: Bacterial Lipoproteinsmentioning
confidence: 99%
“…lactamase activity has been reported in all known mycobacterial species (Kasik, 1979), except the non-pathogenic M. fallax, which exhibits hypersusceptibility to lactams (Quinting et al, 1997). Mycobacteria, including M. tuberculosis, export lactamases to the cell wall via the twin-arginine translocation (Tat) pathway (McDonough et al, 2005, Voladri et al, 1998, thus disruption of the Tat transporter leads to lower lactamase activity in M. smegmatis culture filtrates and increased lactam susceptibility (McDonough et al, 2005). The major lactamase in M. tuberculosis, BlaC, is a member of the Ambler Class-A lactamases and exhibits broad substrate specificity, catalysing hydrolysis of both cephalosporins and penicillins (Voladri et al, 1998, Wang et al, 2006.…”
Section: Lactam Resistance Mechanisms In Mycobacterium Tuberculosismentioning
confidence: 99%